Animal fat in fattening lamb rations - Menzies, C.S. (Kansas Agricultural Experiment Station, 2011)
Animal fats often are added in small amounts (1-2%) to mixed commercial feeds primarily to reduce dustiness and to lubricate machinery. High-energy poultry rations often contain higher levels of animal fat. This test was conducted to obtain more information on fat’s value when added to fattening lamb rations.
Keywords: Lamb; Animal fat; Gain